Long shadows [compact disc, unabridged] - Baldacci, David (Baldacci, David. Amos Decker series., 2022)
When a federal judge and her bodyguard are found dead, the case seems cut and dry. But as witnesses start disappearing, Amos Decker is pulled down a twisted tunnel of secrets, crimes, and scandal.